2015
DOI: 10.1002/jor.22778
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional mesoscale analysis of translamellar cross‐bridge morphologies in the annulus fibrosus using optical coherence tomography

Abstract: The defining characteristic of the annulus fibrosus (AF) of the intervertebral disc (IVD) has long been the lamellar structures that consist of highly ordered collagen fibers arranged in alternating oblique angles from one layer to the next. However, a series of recent histologic studies have demonstrated that AF lamellae contain elastin- and type VI collagen-rich secondary “cross-bridge” structures across lamellae. In this study, we use optical coherence tomography (OCT) to elucidate the three-dimensional (3D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Together with our previous results in ovine IVDs, 19 these data indicate that the ability for OCT to visualize the ITL matrix in AF tissues across species.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Together with our previous results in ovine IVDs, 19 these data indicate that the ability for OCT to visualize the ITL matrix in AF tissues across species.…”
Section: Resultssupporting
confidence: 86%
“…42 Within each lamella at the microscale level, it has been shown that motion segment bending induces fibrillar sliding of collagen on the convex side that is in tension, 34 resulting in greater relative displacements across collagen fibers than within collagen fibers, similar to that which has been observed in tendons. 43,44 At the intermediate mesoscale level, the ITL matrix traverses through and between lamellae, 19 but its mechanical function in the AF during tissue loading is still subject to speculation. Previous studies have suggested that the ITL compartment contributes little to AF mechanics in radial tension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This angle‐ply structure contributes to the nonlinear and anisotropic mechanical properties of the AF . Adding to this structural complexity, individual lamellae are separated by a disorganized interlamellar tissue containing proteoglycan‐rich matrix, elastic fibers, and cells, and are connected by networks of interlamellar cross‐bridges consisting of elastin and type VI collagen, which are thought to be important for maintaining healthy AF function . Elastic fibers are also known to bridge layers, and these have been speculated to be functional tie fibers and/or remnants of vascular channels that regress following IVD development .…”
Section: Introductionmentioning
confidence: 99%